Intervensi Kemampuan Berbicara Anak Berkebutuhan Khusus dalam Pembelajaran Anak Usia Dini di PAUD Mukhtar Syafaat Banyuwangi - Zaidatul Istiqomah, Fina; Muhammad Fauzi Al Hamidi; Luluk Sri Agus Prasetyoningsih (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Speaking skills are closely related to child development. Especially for children with special needs who have delays in their development. One of them is delayed speaking in early childhood. With these problems, intervention is needed to support the development of speaking from an early age. This research concept uses a social model of intervention through an environmental approach. This research aims to 1) How is the speaking ability of ABK in learning. Early childhood in preschool Mukhtar Syafaat, 2) What are the forms of intervention for Children with Special Needs (ABK) through learning approaches for early childhood Mukhtar Syafaat. The research method in this research uses case studies. In this research, researchers used observation, interview and documentation data collection techniques. Data analysis. used is Spradley data analysis including domain analysis, taxonomic analysis, and componential analysis. The results of the research show that the speaking ability of children with special needs in PAUD Mukhtar Syafaat. The speaking ability of children with children with special needs in PAUD Mukhtar Syafaat in the Speech Delay type of children with special needs in communicating with their friends is also still halting. Meanwhile, children who have learning difficulties cannot make complete articulations or the words they say are not clear. The next thing is that autistic children don't want to talk during learning activities because they are still confused when communicating. The forms of intervention include the UDL, Mentessori, TEACCH, ABA, and Son-rice methods. Methods. The intervention used makes children with special needs able to interact like other children.